Community Archive of Social Culture in FISIP UNPAR Through Communication Visual of Zine Creation “Buku, Pesta, Cinta” - Muzadi, Alifya Ainun; Hermawan, Daniel (IC-ITECHS, 2024)
This study explores the role of zines as a medium for archiving the socio-cultural heritage of FISIP UNPAR through the creation of Buku, Pesta, Cinta by the community GRAND BUPESTA. Employing a qualitative descriptive methodology, the research examines how visual communication design is utilized to preserve and convey cultural narratives. The zine features photography and narrative text inspired by the urban legends of FISIP UNPAR, employing provocative yet reflective headlines to engage its audience. Results indicate that zines, as grassroots publications, effectively serve as tools for documenting and disseminating cultural identity, showcasing the potential of visual communication in community archiving efforts.